Exposure of Syrian refugee agricultural workers to pesticides in Lebanon: a socio-economic and political lens - Noory, Bandar; Habib, Rima R.; Nuwayhid, Iman (Frontiers in Public Health, 2024)
This article adopts a socio-economic and political lens to elucidate the interplay of factors that heighten the vulnerability of Syrian refugee agricultural workers and their exposure to pesticides in Lebanon. It provides a comprehensive understanding for the interconnected social, political and economic factors at the global, regional, national and local levels and how they increase the vulnerability of Syrian refugee agricultural workers, particularly their exposure to pesticides. The global factors highlight the shifts from colonialism to state-controlled economies to neoliberal policies. These changes have prioritized the interests of large agricultural schemes and multinationals at the expense of small and medium-sized agriculture. Consequently, there has been a boost in pesticides demand, coupled with weak regulations and less investment in agriculture in the countries of the Global South. The article explains how the dynamic interaction of climate change and conflicts in the Middle East and North Africa region has negatively impacted the agriculture sector and food production, which led to an increased potential for pesticide use. At the national and local levels, Lebanon’s social, political and economic policies have resulted in the weakening of the agricultural sector, the overuse of pesticides, and the intensification of the Syrian refugee agricultural workers’ vulnerability and exposure to pesticides. The article recommends that researchers, policymakers, and practitioners adopt a political-economic-social lens to analyze and address the full dynamic situation facing migrant and refugee workers in Lebanon and other countries and promote equity in the agricultural sector globally.